Rancang Bangun Prototipe Repositori Sederhana Menggunakan Metode Design Thinking Hadis - Wahyudin Darmalaksana; Eva Meidi Kulsum (Gunung Djati Conference Series, 2022)
This study aims to discuss the inspiration of the Prophet's hadith. about the obligation to study in designing a repository as a prototype. This study uses a qualitative approach by applying the Hadith Design Thinking method. The results showed that the hadith about the obligation to study can be an inspiration in designing a repository prototype for systematic knowledge management. The discussion of the research results explains that reading the hadith about the obligation to study using relevant theories has resulted in inspiration in the form of designing a simple prototype repository for systematic knowledge management to become a scientist in the midst of very rapid advances in digital information technology. This study concludes that the use of hadith design thinking is able to explore the understanding of hadith about the obligation to study to produce inspiration for designing a simple repository prototype to be developed into a reputable repository. This research recommends especially for those who are interested in hadith science to develop a design thinking hadith method in taking inspiration from the example of the Prophet Muhammad in designing a prototype through collaboration with experts in the relevant fields of science with continuous testing to find a more appropriate prototype.